Morphology-Controlled WO3 and WS2 Nanocrystals for Improved Cycling Performance of Lithium Ion Batteries - Lim, Young Rok; Ko, Yunseok; Park, Jeunghee; Cho, Won Il; Lim, Soo A.; Cha, EunHee (KOREAN ELECTROCHEMISTRY SOC, 2019)
As a promising candidate for anode materials in lithium ion battery (LIB), tungsten trioxide (WO3) and tungsten disulfide (WS2) nanocrystals were synthesized, and their electrochemical properties were comprehensibly studied using a half cell. One-dimensional WO3 nanowires with uniform diameter of 10 nm were synthesized by hydrothermal method, and two-dimensional (2D) WS2 nanosheets by unique gas phase sulfurization of WO3 using H2S. WS2 nanosheets exhibits uniformly 10 nm thickness. The WO3 nanowires and WS2 nanosheets showed maximum capacities of 552 and 633 mA h g(-1), respectively, after 100 cycles. Especially, the capacity of WS2 is significantly larger than the theoretical capacity (433 mA h g(-1)). We also examined the cycling performance using a larger size WO3 and WS2 nanocrystals, showing that the smaller size plays an important role in enhancing the capacity of LIBs. The larger capacity of WS2 nanosheets than the theoretical value is ascribed to the lower charge transfer resistance of 2D nanostructures.
Keywords: FEW-LAYER WS2; ANODE MATERIALS; ENERGY-STORAGE; ELECTRODE MATERIALS; NANOSHEETS; CARBON; NANOMATERIALS; CYCLABILITY; COMPOSITES; CAPABILITY